Immunological and genetic predictors of breast cancer - A. N. Glushkov; E. G. Polenok; L A. Gordeeva; S. A. Mun; E. N. Voronina; M. V. Kostyanko; A. V. Antonov; N. E. Verzhbitskaya; G. I. Kolpinskiy (Фундаментальная и клиническая медицина, 2022)
Aim. To investigate the associations of idiotypic IgA antibodies against benzo[a]pyrene, estradiol and progesterone (IgA1 -Bp, IgA1 -E2, and IgA1 - Pg) with the corresponding anti-idiotypic IgG antibodies to estradiol and progesterone (IgG2 -E2 and IgG2 -Pg) and with gene polymorphisms of CYP1A1, CYP1A2, CYP1B1, CYP17A1, CYP19A1, GSTM1, GSTT1, and GSTP1 in patients with stage 1 breast cancer. Materials and Methods. Idiotypic and anti-idiotypic antibodies in the serum of 240 healthy women and 505 patients with stage 1 breast cancer were measured by enzyme-linked immunosorbent assay. Prevalence of CYP1A1 (rs4646903), CYP1A2 (rs762551), CYP1B1 (rs1056836), CYP19A1 (rs2470152), GSTM1(del), GSTT1(del), and GSTP1 (rs1695) polymorphisms in 530 healthy women and 694 patients with stage 1 breast cancer were determined by real-time polymerase chain reaction.Results. Low personal IgA1 -Bp/IgA1 -Pg < 1 and IgA1 -E2/IgA1 -Pg < 1 ratios in combination with low IgG2 -E2 ≤ 4 and high IgG2 -Pg > 2 levels were found in 20.6% of healthy women and in 4.5% of breast cancer patients (p < 0.0001; OR = 0.2). Low IgA1 -Bp/IgA1 -Pg and high IgA1 -E2/IgA1 -Pg ratios in combination with low IgG2 -E2 and high IgG2 - Pg levels were revealed in 7.4% of healthy women and 2.8% of breast cancer patients (p = 0.009; OR = 0.4). These two variants were integrated and marked as protective immunological phenotype. High IgA1 - Bp/IgA1 -Pg and high IgA1 -E2/IgA1 -Pg ratios combined with high IgG2 -Pg and high or low IgG2 -E2 levels were found in 17.2% of healthy women and27.2% of breast cancer patients (p = 0.006; OR = 1.8) and in 6.4% of healthy women and in 18.3% of breast cancer patients (p < 0.0001; OR = 3.3), correspondingly. These two variants were integrated and marked as pro-carcinogenic immunological phenotype. These associations were found only with estrogen receptor-positive (ER+) breast cancer. GSTP1 (rs1695) gene polymorphism was associated exclusively with estrogen receptor-negative (ER-) breast cancer (p = 0.004; OR = 1.56). No interrelations be tween immunological phenotypes and studied polymorphisms of CYP and GST genes have been found.Conclusion. Pro-carcinogenic immunological phenotype and rs1695 gene polymorphism within the GSTP1 gene were independent predictors of ER+ and ER- breast cancer correspondingly.